Evolution of Effectiveness of the Self-Evaluation Examination: A Mixed Methods Study of Predictive Validity and Perceived Utility. - McMullan, Susan P.; Muckle, Timothy J.; Wofford, Kenneth A.; Ward, Robyn C.; Chan, Janet (AANA Journal, 2025)
The Self-Evaluation Examination (SEE), an in-training examination administered by the National Board of Certification and Recertification of Nurse Anesthetists (NBCRNA), was reconfigured in 2016 to ensure fulfillment of its intended purposes, improve its utility, and augment predictive value toward a first-time pass on the National Certification Examination (NCE). The purpose of this mixed methods study was to reenvision the SEE to further enhance its value to stakeholders. A correlational quantitative analysis was conducted between the reconfigured SEE and NCE. A qualitative analysis of survey results was also performed; focus groups were undertaken among program administrators to assess utilization of the SEE. Final SEE results for 8,552 students from September 2016 through October 2023 were linked to first-time NCE results. Pearson's r correlations (r = 0.57; P < .01) represent a moderately strong positive correlation between SEE and NCE performance. Data from a survey of 107 program administrators indicated positive support for reconfigured SEE. Themes from three focus groups identified uses, best practices, and desired enhancements. Results were consistent with previously reported results, confirming the reconfigured SEE met intended goals. Future augmentations are being considered by NBCRNA to further enhance utility and value to nurse anesthesia educational programs.